Bài 1: Tìm m để các phương trình sau: i) có nghiệm; ii) vô nghiệm
a) (m – 5) x^2 – 4mx +m – 2=0
b) (m -2) x^2 +2 ( 2- 3m)x +5m – 6 =0
c) ( 3 – m) x^2 -2 ( m+3) x+m+2 =0
d) (1 +m) x^2 – 2mx +2m =0
e) ( m-2)x^2 – 4mx + 2m – 6= 0
f) ( -m^2 +2m -3) x^2 + 2 ( 2- 3m) x-3 =0
Giúp e giải vs ạ!! Cảm ơn!
Đáp án:
ii. \(f.m \in \left( {\frac{{3 – \sqrt {39} }}{6};\frac{{3 + \sqrt {39} }}{6}} \right)\)
Giải thích các bước giải:
\(\begin{array}{l}
i.a.4{m^2} – \left( {m – 5} \right)\left( {m – 2} \right) \ge 0\\
\to 3{m^2} + 7m – 10 \ge 0\\
\to m \in \left( { – \infty ; – \frac{{10}}{3}} \right] \cup \left[ {1; + \infty } \right)\\
b.4 – 12m + 9{m^2} – \left( {m – 2} \right)\left( {5m – 6} \right) \ge 0\\
\to 4{m^2} + 4m – 8 \ge 0\\
\to m \in \left( { – \infty ; – 2} \right] \cup \left[ {1; + \infty } \right)\\
c.{m^2} + 6m + 9 – \left( {3 – m} \right)\left( {m + 2} \right) \ge 0\\
\to 2{m^2} + 5m + 3 \ge 0\\
\to m \in \left( { – \infty ; – \frac{3}{2}} \right] \cup \left[ { – 1; + \infty } \right)\\
d.{m^2} – \left( {1 + m} \right)\left( {2m} \right) \ge 0\\
\to – {m^2} – 2m \ge 0\\
\to m \in \left[ { – 2;0} \right]\\
e.4{m^2} – \left( {m – 2} \right)\left( {2m – 6} \right) \ge 0\\
\to 2{m^2} + 10m – 12 \ge 0\\
\to m \in \left( { – \infty ; – 6} \right] \cup \left[ {1; + \infty } \right)\\
f.4 – 12m + 9{m^2} + 3\left( { – {m^2} + 2m – 3} \right) \ge 0\\
\to 6{m^2} – 6m – 9 \ge 0\\
\to m \in \left( { – \infty ;\frac{{3 – \sqrt {39} }}{6}} \right] \cup \left[ {\frac{{3 + \sqrt {39} }}{6}; + \infty } \right)\\
ii.a.m \in \left( { – \frac{{10}}{3};1} \right)\\
b.m \in \left( { – 2;1} \right)\\
c.m \in \left( { – \frac{3}{2}; – 1} \right)\\
d.m \in \left( { – \infty ; – 2} \right) \cup \left( {0; + \infty } \right)\\
e.m \in \left( { – 6;1} \right)\\
f.m \in \left( {\frac{{3 – \sqrt {39} }}{6};\frac{{3 + \sqrt {39} }}{6}} \right)
\end{array}\)